Neutralizing and Targeting Properties of a New Set of α4β7-Specific Antibodies Are Influenced by Their Isotype. (1st May 2017) - Girard, Alexandre; Jelicic, Katija; Van Ryk, Don; Rochereau, Nicolas; Cicala, Claudia; Arthos, James; Noailly, Blandine; Genin, Christian; Verrier, Bernard; Laurant, Stephanie; Razanajaoana-Doll, Diane; Pin, Jean-Jacques; et al.
Abstract : Abstract: The homing of lymphocytes to the mucosa is mainly controlled by α4β7 integrin, and it is amplified during gut chronic inflammation, as occurs with HIV and/or inflammatory bowel diseases. We designed and applied an improved immunization strategy based on an innovative selection process to isolate new α4β7 + lymphocyte–specific monoclonal antibodies that are able to prevent their migration into inflamed gut tissues and/or to counteract HIV infection in vitro. First, 5 monoclonal antibodies (1 IgA, 1 IgM, and 4 IgGs) were selected based on their capacity to recognize α4 or β7 homodimers and α4β7 heterodimers in transfected human cells. Their ability to block gp120/α4β7 or MAdCAM-1/α4β7 interactions was then measured in vitro with human T and B lymphocytes. In vitro, the anti-α4β7 IgA isotype was found to have the highest affinity for the α4β7 heterodimer, and it significantly reduced HIV replication in retinoic acid–treated α4β7 hi CD4 + human T cells. This α4β7-specific IgA also displayed a high avidity for human and mouse α4β7 + lymphocytes in both mouse and human inflammatory colitis tissues. These new antibodies, and in particular those with mucosa-targeting isotypes such as IgA, could therefore be potential novel therapeutic tools for treating HIV and inflammatory bowel disease. Abstract : Supplemental Digital Content is Available in the Text.